Strategic ignorance and perceived control - Balietti, Anca; Budjan, Angelika J.; Eymess, Tillmann; Soldà, Alice (AWI discussion paper series, 2023)
Information can trigger unpleasant emotions. As a result, individuals might be tempted to strategically ignore it. We experimentally investigate whether increasing perceived control can mitigate strategic ignorance. Participants from India were presented with a choice to receive information about the health risk associated with air pollution and were later asked to recall it. Perceived control leads to a substantial improvement in information recall. We find that optimists react most to perceived control, both with a reduction in information avoidance and an increase in information recall. This latter result is supported by a US sample. A theoretical framework rationalizes our findings.
Keywords: Graue Literatur